Issues of Inclusive Education in Manipur - Bidyabati, Wangkheirakpam; Singh, Lairellakpam Seilendra (THE PRIMARY TEACHER, 2017)
Inclusive education is a comparatively new concept. The educational practice entails integration of Children With Special Needs (CWSN) in regular classrooms. The philosophy rests on the idea that every individual, regardless of one’s socioeconomic and religious backrounds, and physical and mental abilities has the right to be provided education along with everybody else. It is, therefore, about building a society with equal opportunities and social cohesion. The study aims to find out issues challenging inclusive education, as regards to disabled students, in schools located in Manipur’s Imphal East and West districts. A survey was conducted by administering a self-made questionnaire in schools, where CWSN are enrolled. It was found that there are many issues that adversely affect the inclusion of CWSN in regular schools. The findings revealed that none of the schools have trained teachers and resource persons, or prepare Individualised Education Plans for CWSN. The results also revealed low assessment and high dropout rate among CWSN.